H.G. Wells and all things Russian - Diment, Galya (London ; New York, NY : Anthem Press, an imprint of Wimbledon Publishing, 2019)
'H. G. Wells and All Things Russian' examines Wells's keen interest in Russian culture and development, and how Russia and the Soviet Union were, in turn, profoundly influenced by his works and his visits to the country
Yevgeny Zamyatin and the Wellsian utopia / Maxim Shadurski -- Time machines and metamorphoses: H.G. Wells's influence on Mikhail Bulgakov and Sigizmund Krzhizhanovsky / Muireann Maguire -- "The Wellsian twist in Nabokov's "Terra Incognita" / Zoran Kuzmanovich -- "Unregenerate mass nature" in H.G. Wells and the Brothers Strugatsky / Richard Boyechko -- Culturology: Yuly Kagarlitsky's Life of Wells / Patrick Parrinder -- "Come and visit us in ten years' time!": Representation of H.G. Wells on the Russian Stage and Screen / Olga Sobolev and Angus Wrenn -- Present tense arguments: Russia and H.G. Wells's Babes in the Darkling Wood / David Rampton -- Wells and Gorky / Ira Nadel -- Odette Keun versus H.G. Wells on Russia / Galya Diment
Work consists of both items originally published in English and other items newly translated to English from the original Russian.
Includes bibliographical references and indexes
Print version record
JSTOR
Keywords: Wells, H. G. -- 1866-1946 -- Knowledge -- Soviet Union; Wells, H. G. -- 1866-1946 -- Criticism and interpretation -- History; Wells, H. G. -- 1866-1946 -- Influence; Wells, H. G. -- 1866-1946; Soviet literature -- English influences; English literature -- Soviet influences; Littérature soviétique -- Influence anglaise; LITERARY CRITICISM -- Comparative Literature; English literature -- Soviet influences; Influence (Literary, artistic, etc.); Soviet Union; Literary criticism; Criticism, interpretation, etc; History; Literary criticism; Critiques littéraires.